Correction of nonuniformity error of Gafchromic EBT2 and EBT3 - Katsuda, Toshizo (J Appl Clin Med Phys, 2016)
This study investigates an X‐ray dose measurement method for computed tomography using Gafchromic films. Nonuniformity of the active layer is a major problem in Gafchromic films. In radiotherapy, nonuniformity error is reduced by applying the double‐exposure technique, but this is impractical in diagnostic radiology because of the heel effect. Therefore, we propose replacing the X‐rays in the double‐exposure technique with ultraviolet (UV)‐A irradiation of Gafchromic EBT2 and EBT3. To improve the reproducibility of the scan position, Gafchromic EBT2 and EBT3 films were attached to a 3‐mm‐thick acrylic plate. The samples were then irradiated with a 10 W UV‐A fluorescent lamp placed at a distance of 72 cm for 30, 60, and 90 minutes. The profile curves were evaluated along the long and short axes of the film center, and the standard deviations of the pixel values were calculated over large areas of the films. Paired t‐test was performed. UV‐A irradiation exerted a significant effect on Gafchromic EBT2 (paired t‐test; [Formula: see text]) but not on EBT3 (paired t‐test; [Formula: see text]). Similarly, the homogeneity was improved in Gafchromic EBT2 but not in EBT3. Therefore, the double‐exposure technique under UV‐A irradiation is suitable only for EBT2 films. PACS number(s): 87.53 Bn